Transient Receptor Potential Melastatin 4 Channel Controls Calcium Signals and Dental Follicle Stem Cell Differentiation123. (19th December 2012) - Nelson, Piper; Ngoc Tran, Tran Doan; Zhang, Hanjie; Zolochevska, Olga; Figueiredo, Marxa; Feng, Ji‐Ming; Gutierrez, Dina L.; Xiao, Rui; Yao, Shaomian; Penn, Arthur; Yang, Li‐Jun; Cheng, Henrique
Abstract Elevations in the intracellular Ca2+ concentration are a phenomena commonly observed during stem cell differentiation but cease after the process is complete. The transient receptor potential melastatin 4 (TRPM4) is an ion channel that controls Ca2+ signals in excitable and nonexcitable cells. However, its role in stem cells remains unknown. The aim of this study was to characterize TRPM4 in rat dental follicle stem cells (DFSCs) and to determine its impact on Ca2+ signaling and the differentiation process. We identified TRPM4 gene expression in DFSCs, but not TRPM5, a closely related channel with similar function. Perfusion of cells with increasing buffered Ca2+ resulted in a concentration‐dependent activation of currents typical for TRPM4, which were also voltage‐dependent and had Na+ conductivity. Molecular suppression with shRNA decreased channel activity and cell proliferation during osteogenesis but not adipogenesis. As a result, enhanced mineralization and phosphatase enzyme activity were observed during osteoblast formation, although DFSCs failed to differentiate into adipocytes. Furthermore, the normal agonist‐induced first and secondary phases of Ca2+ signals were transformed into a gradual and sustained increase which confirmed the channels' ability to control Ca2+ signaling. Using whole genome microarray analysis, we identified several genes impacted by TRPM4 during DFSC differentiation. These findings suggest an inhibitory role for TRPM4 on osteogenesis while it appears to be required for adipogenesis. The data also provide a potential link between the Ca2+ signaling pattern and gene expression during stem cell differentiation. STEM Cells2013;31:167–177